2021
DOI: 10.1155/2021/8886792
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Calculation Method of Meshing Stiffness for the Beveloid Gear considering the Effect of Surface Topography

Abstract: The tooth surfaces of beveloid gears have different topography features due to machining methods, manufacturing accuracies, and surface wear, which will affect the contact state of the tooth surface, thereby affecting time-varying mesh stiffness between mating gear pairs. Therefore, a slice grouping method was proposed in this paper on the basis of potential energy to calculate the total meshing stiffness of beveloid gears with the surface topography. The method in this paper was verified by finite element met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Nutation face gear belongs to a kind of face gear, and the rough surface in the contact area is a series of discrete points when the nutation face gear transmission engages, so the meshing line can be approximated as a curve. Through literature analysis (Mao, 2022), it can be concluded that in practical calculations, the three-dimensional fractal function needs to be improved and dimensionally reduced before using. Therefore, when calculating the meshing stiffness of the nutation face gear considering roughness, the rough surface three-dimensional fractal function was not used to characterize the model.…”
Section: Methodsmentioning
confidence: 99%
“…Nutation face gear belongs to a kind of face gear, and the rough surface in the contact area is a series of discrete points when the nutation face gear transmission engages, so the meshing line can be approximated as a curve. Through literature analysis (Mao, 2022), it can be concluded that in practical calculations, the three-dimensional fractal function needs to be improved and dimensionally reduced before using. Therefore, when calculating the meshing stiffness of the nutation face gear considering roughness, the rough surface three-dimensional fractal function was not used to characterize the model.…”
Section: Methodsmentioning
confidence: 99%
“…A slice grouping method based on potential energy was advanced to calculate the TVMS considering fractal tooth surface in Ref. [36]. Yang et al [37] developed a contact stiffness calculation model of two arc gears considering friction based on an improved fractal contact model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Wu et al [32] proposed an improvement to the elastic deformation formula for calculating the meshing stiffness of cylindrical gears. Mao et al [33] improved the Weber method based on the slicing principle. However, these methods can only accomplish the calculation of the meshing stiffness of variable beveloid gears with specific parameters and the systematic and generalized approach still presents a gap.…”
Section: Introductionmentioning
confidence: 99%
“…The finite element method (FEM) is the widely-chosen method among the various numerical methods for calculating the meshing stiffness of beveloid gears [34][35][36][37]. However, these researchers only analyzed models with specific parameters.…”
Section: Introductionmentioning
confidence: 99%